2021
DOI: 10.1016/j.enbuild.2021.111249
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Data-driven school building stock energy and indoor environmental quality modelling method

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…16,17 The building envelope materials have been assumed from Schwartz, Y. et al, 2021. 18 and occupancy schedules were taken from NCM schedules for primary schools, included in Design Builder. 17 The weather file dates from 2002.…”
Section: Pv and School Modellingmentioning
confidence: 99%
“…16,17 The building envelope materials have been assumed from Schwartz, Y. et al, 2021. 18 and occupancy schedules were taken from NCM schedules for primary schools, included in Design Builder. 17 The weather file dates from 2002.…”
Section: Pv and School Modellingmentioning
confidence: 99%
“…This paper builds on a significant body of work undertaken to date to explore energy performance in the school stock (Hong et al 2022;Schwartz et al 2021Schwartz et al , 2022Godoy-Shimizu et al 2021). It uses a highly detailed database to examine the potential for reducing emissions, with a focus on primary and secondary schools in England, which account for approximately 85% of schools in England by count (DfE 2017).…”
Section: (Dfe 2022a)mentioning
confidence: 99%
“…An archetype London primary school was also used to test a new exergy-based retrofit model, capable of considering factors such as economic impact and thermal comfort as part of multi-optimisation analyses (Kerdan et al 2016(Kerdan et al , 2017. More recently, a school stock model was produced using 168 archetypes for the primary school stock of England (Schwartz et al 2021). This was expanded to evaluate overheating risk and indoor environmental quality (IEQ) metrics, and showed that energy retrofits (specifically wall insulation, double-glazing and external shading) could negatively impact IEQ and, conversely, that some IEQ measures will increase heating demand (Grassie et al 2022).…”
Section: (Dfe 2022a)mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, construction is a sector that can make a significant contribution to reducing greenhouse gas emissions [42][43][44][45][46][47][48]. This is due to potential of this sector to implement solutions characterized by rapid impact and high-cost efficiency, which mainly include measures to increase the energy efficiency of buildings [49][50][51][52][53][54][55][56][57][58]. Two groups can be distinguished among them: one related to the design and construction of new buildings and one related to the renovation of existing buildings.…”
Section: Reducing Greenhouse Gas Emissions In the Construction Sectormentioning
confidence: 99%